Nicotinamide Riboside and Phycocyanin Oligopeptides Affect Stress Susceptibility in Chronic Corticosterone-Exposed Rats - Orhan, Cemal; Sahin, Emre; Tuzcu, Mehmet; Şahin, Nurhan; Celik, Abdullah; Ojalvo, Sara Perez; Şahin, Kazım (Mdpi, 2023)
Nicotinamide riboside (NR) is an NAD+ precursor capable of regulating mammalian cellular metabolism. Phycocyanin oligopeptide (PC), a phytonutrient found in blue-green algae, has antioxidant and anti-inflammatory properties. This study explored the effects of NR, PC, and their combination on the telomere length as well as inflammatory and antioxidant status of rats under chronic stress conditions (CS). Forty-nine rats were allocated into seven groups: control, chronic stress (CS), CS with NR (26.44 mg/kg), a low dose of 2.64 mg/kg of PC (PC-LD), or a high dose of 26.44 mg/kg PC (PC-HD), NR + PC-LD, and NR + PC-HF. The rats were given daily corticosterone injections (40 mg/kg) to induce stress conditions, or NR and PC were orally administered for 21 days. NR and PC supplementation, particularly NR plus PC, increased the serum antioxidant enzyme activities, hepatic nicotinamide adenine (NAD+) content, and telomere length (p < 0.001 for all) compared to the CS group. The levels of serum malondialdehyde (MDA), liver interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-alpha), IL-1 beta, and IL-8 were reduced under the CS condition (p < 0.001). In addition, CS decreased the levels of hepatic telomere-related proteins and sirtuins (SIRT1 and 3), whereas administration of NR and PC or their combination to CS-exposed rats increased the levels of telomere-related proteins (e.g., POT1b, TRF1 and TRF2), SIRT3 and NAMPT (p < 0.05). In conclusion, NR and PC, especially their combination, can alleviate metabolic abnormalities by enhancing hepatic cytokines, SIRT3, NAMPT, and NAD+ levels in CS-exposed rats. More research is needed to further elucidate the potential health effects of the combination of NR and PC in humans.
Keywords: corticosterone; phycocyanin; nicotinamide riboside; NAD; hepatic metabolism